Neoadjuvant chemoradiotherapy for resectable gastric cancer: A meta-analysis - Jiuzhou Chen; Jiuzhou Chen; Yaru Guo; Yaru Guo; Miao Fang; Miao Fang; Yan Yuan; Yan Yuan; Youqi Zhu; Youqi Zhu; Yong Xin; Yong Xin; et al. (Frontiers in Oncology, 2022)
ObjectivesTo evaluate the clinical curative effects and toxicity of neoadjuvant chemoradiotherapy for resectable gastric cancer compared to those of neoadjuvant chemotherapy.MethodsA systematic review and meta-analysis of the randomized controlled trials (RCTs) of neoadjuvant chemoradiotherapy versus neoadjuvant chemotherapy were performed in patients with resectable gastric cancer.ResultsSeven RCTs were included (601 patients; 302 in the neoadjuvant chemoradiotherapy group and 299 in the neoadjuvant chemotherapy group). The neoadjuvant chemoradiotherapy group had an increased number of patients with a complete response [odds ratio (OR) = 3.79, 95% confidence interval (CI): 1.68–8.54, p = 0.001] and improved objective response rate (OR = 2.78, 95% CI: 1.69–4.57, p < 0.0001), 1-year (OR = 3.51, 95% CI: 1.40–8.81, p = 0.007) and 3-year (OR = 2.14, 95% CI: 1.30–3.50, p = 0.003) survival rates, R0 resection rate (OR = 2.21, 95% CI: 1.39–3.50, p = 0.0008), and complete pathologic response (OR = 4.39, 95% CI: 1.59–12.14, p = 0.004). Regarding the incidence of adverse effects after neoadjuvant therapy, only the occurrence rate of gastrointestinal reaction in the neoadjuvant chemoradiotherapy group was higher than that in the neoadjuvant chemotherapy group (OR = 1.76, 95% CI: 1.09–2.85, p = 0.02), and there was no significant difference in other adverse effects. There was no difference in the incidence of postoperative complications between the two groups.ConclusionNeoadjuvant chemoradiotherapy for resectable gastric cancer has several advantages in terms of efficacy and safety compared to neoadjuvant chemotherapy. Therefore, neoadjuvant chemoradiotherapy has great potential as an effective therapy for resectable gastric cancers.Systematic Review Registrationhttps://inplasy.com/inplasy-2022-3-0164, registration number INPLASY202230164.